Gastroinstestinal Bleeding in Pediatrics - Muzal Kadim (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Gastrointestinal bleeding (GI) may occurs in infants and children. Most etiologies of GI bleeding are mild and self-limited, but may advance into life-threatening condition if not treated properly. Upper GI bleeding and lower GI bleeding can be classified based on bleeding sites that is above or below Treitz ligament. Causes of GI bleeding in infants and children varies according to their age and bleeding sites. Some conditions may be misunderstood as GI bleed such as consumption of certain red coloured food. Diagnosis of gastrointestinal bleeding in children includes complete history taking, thorough physical examination, laboratory examination, radiological examination, and other supportive modality such as endoscopy. Early diagnosis and proper therapy can improve outcomes and prevent severe conditions.